Procrastination and Psychosocial Outcomes: Mental Health and Emotional Intelligence Correlates - Khan, Kavya (Journal of Educational Research and Policies, 2025)
Objectives: 1. To examine procrastination's impact on college students' mental health. 2. To determine procrastination's impact on college students' emotional intelligence. Hypotheses: 1. There will be no significant difference between high and low procrastination in mental health. 2. There will be no significant difference between high and low procrastination on emotional intelligence. Sample: For the present study, 100 subjects were selected from Nashik City, Maharashtra State. The adequate sample consisted of 100 subjects (Procrastination was used as a scrutiny test), 50 high - procrastination college students, and 50 low - procrastination college students. The age range of subjects was 18 to 23 (Mean 19.35, SD = 2.06). Research Tools: Samvaidna’s Procrastination Scale (Abrahim, 2013): 2. Mental Health Inventory: constructed by Dr. Jagdish and Dr. A K Srivastav. Pedhe and Hyde were used to measure Emotional intelligence. Conclusion: 1. low procrastination was associated with significantly higher mental health scores compared to high procrastination among college students.2. low procrastination is associated with significantly higher emotional intelligence than high procrastination among college students.